Pemikiran tasawuf Nuruddin Ar-raniry: Relevansi dengan perkembangan islam di nusantara - Sya'bana, Salsabila Dewi (Maliki Interdisciplinary Journal, 2025)
This article examines the Sufi thought of Sheikh Nuruddin Ar-Raniry, a prominent 17th-century scholar who played an important role in the development of Islam in Aceh and the archipelago. This study analyzes his biography and educational background, the main concepts in his teachings, and the influence of his teachings on Islam in Aceh and the archipelago. Ar-Raniry was known for his opposition to doctrine. The main concepts in his Sufism include his views on God, nature, and humanity. He sought to bridge theological and Sufi thought, interpreting the concept of tajalli (manifestation) of Allah, and viewing humans as the most perfect creatures and caliphs of Allah. Ar-Raniry strongly emphasized that sharia is the absolute foundation of Sufism, and he criticized the misinterpretation of the teachings of Wujudiyyah. The influence of his teachings was significant, including the purification of faith, the strengthening of Islamic law, and the development of Islamic literacy in the Malay language through his writings, which became an important part of the Islamic education curriculum.